Does a connection exist among national culture, alliance strategy, and leading ICT firms’ performance - Golonka, Monika; Rzadca, Robert (Journal of Business Economics and Management, 2017)
"Corrigendum." Journal of Business Economics and Management, 18(1), p. 180